Integrating Short Sea Shipping with Trans-European Transport Networks - Tiago A. Santos; Miguel Â. Fonseca; Pedro Martins; C. Guedes Soares (Journal of Marine Science and Engineering, 2022)
This paper studies the possibilities of closer integration of short sea shipping, with other components of the Trans-European Transport Networks, shifting a significant share of road freight onto rail corridors and inland waterways. A numerical model of transport networks is used to support the calculation of the main parameters driving transport decisions, for multiple pairs of origin/destination representing statistical regions of the European Union, and for different, alternative intermodal and unimodal transport chains. Results are presented using a geographic information system. This approach is applied in a case study dedicated to the evaluation of the competitiveness of transport chains based on short sea shipping between Portugal and The Netherlands, integrated with other components of Trans-European Transport Networks (rail freight corridors and inland waterways), compared to road haulage-based transport chains. Conclusions are drawn regarding the geographical scope of the relative competitiveness of these transport chains and policy investment insights are presented.